MP40: Psychological distress in patients following pulmonary embolism diagnosis. (May 2019) - Tran, A.; Redley, M.; de Wit, K.
Abstract : Introduction : Pulmonary embolism (PE) is a treatable condition, with a low mortality rate (of around 1% in those who are diagnosed with the condition). The risk of recurrent PE is well managed with long term anticoagulation. Past literature suggests that patients who are diagnosed with PE can go on to experience existential anxiety and symptoms suggestive of post-traumatic stress disorder (PTSD). This study aimed to evaluate the mental and emotional experiences of PE patients through the lens of PTSD, and the factors involved in psychological distress following a PE diagnosis.Methods : Semi-structured interviews were conducted with PE patients at the Juravinski Hospital thrombosis clinic in Hamilton, Ontario. Interview questions were based on DSM-5 criteria of PTSD and relevant existing literature. The transcripts were analyzed by two researchers based on an approach that considers both the content of patients' accounts as well as the way that patients choose to interpret and deliver those accounts, to develop major themes associated with psychological distress.Results : A total of 37 patients, ranging from 28 to 85 years of age, were interviewed. The patients' accounts suggested that the manner in which a PE diagnosis was delivered by an emergency physician was a significant factor in the degree to which they experienced psychological distress. For example, patients reported focusing on words suggesting that they were 'a ticking time-bomb' or that 'a lot of people don't get through this, ' which introduced a degree of panic. A number of patients continued to focus on these words, months or years after their diagnosis. Some feared that they could have recurrent PE which could lead to death. Diagnoses that were delivered calmly with thorough explanations of why a patient experienced PE-related symptoms and how they will be treated, helped to minimize any subsequent anxiety. Patients initially misdiagnosed with an alternative condition in the ED also expressed feelings of anxiety and distress. The presence of physically and mentally distressing symptoms was also a factor which contributed to mental distress and anxiety regarding a PE recurrence.Conclusion : Caution should be taken in the delivery of PE diagnosis in the emergency department. Over-emphasis on the severity and life-threatening nature of PE should be avoided to reduce psychological distress.